Understanding The Rukyatu Al-Hilāl Hadith: Case Study in Darussalam Islamic Boarding School, South Aceh Regency - Nawir Yuslem; Sulidar Sulidar; Muliadi A. (Al-Bukhari : Jurnal Ilmu Hadis, 2022)
This paper discusses how the Darussalam Islamic Boarding School understands the hadiths of Rukyatu al-Hilāl and the practice of Rukyatu al-Hilāl in the field using a thematic hadith approach. The author traces the hadiths about Rukyatu al-Hilāl and there are several versions. This article discusses, How is the understanding of the hadiths of Rukyatu al-Hilāl? What is the reason that the Darussalam Islamic Boarding School in South Aceh did not follow the decision of the Government about Itsbāt? How Rukyatu al-Hilāl in Darussalam Islamic Boarding School is practiced. The results showed that the understanding of the traditions of Rukyatu al-Hilāl according to the Darussalam Islamic Boarding School, was first understood by the al-Quran approach, the second understood by the thematic hadith approach, and the third understood by the atsar.